BONE NAIL SIZE MEASUREMENT SYSTEM BASED ON MACHINE VISION - Yan, Piao; Hao, Yang; Yulong, Tan; Zehan, Zheng; Jingcheng, Yang (International Journal of Engineering Technologies and Management Research, 2025)
Aiming at the problems of low measurement efficiency and poor accuracy consistency in the traditional measurement methods of medical bone nails, a set of bone nail size measurement system based on machine vision was developed. Firstly, the edge position of the bone nail was located by setting the ROI area. Then the Canny algorithm is used to extract the edge accurately, and the edge points are screened by threshold, and the edge points are fitted into straight line segments by least square method for size measurement. Finally, using the Halcon image software platform, the shape matching method was used to match and locate the bone nails, and the batch detection of bone nails was realized. The experimental results show that the measurement accuracy of the system is up to ±0.01mm, the average detection time of a single picture is 54ms, the measurement accuracy is high, the running speed is fast, and it can meet the demand of industrial real-time detection.